Mite to «Stater»: polemical notes on the current presentation of the monument of the XVII century - A. A. Krasilnikova (Библиосфера)
A review of the Permian edition as a religious art monument dated the late XVII century «Statyr» is given. Considered are its positive and negative aspects in the context of the reader's expectations. Assessed is the significance of «Statyr» publication for studying the XVII century monument of the oratory art.